(untitled) (Research, Society and Development, 2020)
Objective: To develop interactive technology of care to strengthen the mother-baby bond in the hospitalization process in a Neonatal Intensive Care Unit, based on scientific literature and based on the perceptions of mothers and the health team. Method: This is an exploratory-descriptive, qualitative research, carried out between October / 2016 and June / 2017, through individual interviews with a group of 16 professionals from the multiprofessional health team and a group of 22 mothers with children admitted to a Neonatal Intensive Care Unit of a large hospital located in the central region of Rio Grande do Sul. Results: The qualitative research process, combined with the literature review, resulted in the development of an interactive care technology, called “ Mother-baby bond: a care history ”, with the purpose of strengthening the mother-baby bond in the hospitalization process in a Neonatal Intensive Care Unit. Final considerations: The concept of a mother-baby bond in a Neonatal Intensive Care Unit transcends the technical care of the multidisciplinary team. The bond was understood as a unique and interactive process that expands and strengthens as mothers are welcomed and included by the multiprofessional team in the intensive care process.